IMPLEMENTING CONTEMPORARY AKHLAK EDUCATION VALUES AT STIT AL HIKMAH TERBING TINGGI - Hasibuan, Ahmad Ibrahim (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: Islamic education significantly emphasizes the development of akhlak, integrating individuals who complete this education into society. Purpose: This research describes the values of contemporary akhlak (moral) education at STIT Al Hikmah Tebing Tinggi. Method: The researchers used a qualitative method with a phenomenological approach in this study. Result: Based on the research results, it was concluded that in order for Islamic universities to become a forum for forming students with contemporary akhlak (moral)’s, universities must determine the standards of akhlak (moral) education values that can be implemented. STIT Al Hikmah Tebing Tinggi, in this case, emphasizes religious values, academic honesty values, and tolerance values. The following strategy is needed to implement these values: First, build a cultural paradigm of akhlakul karimah. These conditions can give birth to superior ideas that can create the Islamic higher education that leaders want. Second, when building academic ethics, when establishing social relationships in the community, especially in educational institutions, the student's inability to see an object as a whole is a form of big mistake and a model of arrogance that assumes that only his own point of view is the most correct. If someone internalizes this mindset, they can tend to blame and negate other points of view. During Rahmatallilalamin's mission, this mission can build the values of Islamic civilization, so in this case, the reality that exists in society was designed by Allah for the dynamics of human life. Pluralism is an unavoidable aspect of society's reality. Conclusion: To realize diversity in society, students must develop an attitude of tolerance so that they feel like they live together and, more importantly, that it is formed within themselves